A mass balance approach for calculation of recovery and binding enables the use of ultrafiltration as a rapid method for measurement of plasma protein binding for even highly lipophilic compounds - Wang, Changguang (2012)
The aim of this study is to further validate the use of ultrafiltration (UF) as a method for determining plasma protein binding (PPB) by demonstrating that non-specific binding (NSB) is not a limitation, even for highly lipophilic compounds, because NSB sites on the apparatus are passivated in the presence of plasma. Mass balance theory was used to calculate recovery of 20 commercial and seven investigational compounds during ultrafiltration in the presence and absence of plasma. PPB was also measured using this mass balance approach for comparison to PPB determined by rapid equilibrium dialysis (RED) and as found in the literature. Compound recovery during UF was dramatically different in the presence and absence of plasma for compounds with high NSB in PBS only. A comparison of PPB calculated by ultrafiltration with literature values or calculated by RED gave concordant results. Discrepancies could be explained by changes in pH, insufficient time to equilibrium, or compound instability during RED, problems which were circumvented by ultrafiltration. Therefore, NSB, as measured by the traditional incubation of compound in PBS, need not be an issue when choosing UF as a PPB assay method. It is more appropriate to calculate compound recovery from the device in plasma as measured by mass balance to determine the suitability of the method for an individual compound. The speed with which UF can be conducted additionally avoids changes in pH or compound loss that can occur with other methods. The mass balance approach to UF is thus a preferred method for rapid determination of PPB.